Analisis Soal Ujian Nasional Matematika Tingkat Smp/MtsTahun 2013-2015 Berdasarkan Perspektif Higher Order Thinking Skill (Hots) - Qoni'ah, Luqmana, Prof.Dr.Budi Murtiyasa,M.Kom (2017)
National Examination is a measurement of national standards in achieving quality of learners, then there should have been a matter of components with high-level thinking skills. This refers to students' Indonesian ability who were in the measurement based on PISA and TIMSS. The purpose of this study was to analyze the matter of Mathematics in SMP/MTs during the years of 2013-2015 based on the perspective HOTS. The method used in this research was document's analysis and the data collection derived from interview with personal person in Mathematic Education. The analysis technic of this research used three steps, there are data reduction, data presentation and data verification. For certify the data collection in this research used technic of triangulation resources. The results of this study indicated that the matter of Mathematics in SMP/MTs during the years of 2013-2015 based on the perspective HOTS be dominated with geometry. In analyse also be find on question in the same type at National Examination in 2013-2015, it shown if the writer is less creativity in made the question according the type of question especially in form of stimulation. The result of this study indicatetd that the National Examination's perspective HOTS in 2013 was (7.5%), the National Exam in 2014 was (12.5%) and the National Examination 2015 was (10%). That is shown the numbers questions of HOTS doesn't consistent. Keywords: higher order thinking skills, national exam, critical thinking, creative thinking